2013
DOI: 10.3102/0034654313497517
|View full text |Cite
|
Sign up to set email alerts
|

Educational Accommodations for Students With Behavioral Challenges

Abstract: Educational policies mandate the consideration of accommodations so that students with disabilities become proficient in the objectives outlined by state academic content standards and demonstrate proficiency on high-stakes assessments. However, neither policies nor empirical research provide sufficient guidance for educators to effectively select and implement accommodations. This study reviews the effectiveness of accommodations for students in the special education eligibility category of emotional disturba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 116 publications
(82 citation statements)
references
References 88 publications
(131 reference statements)
2
78
1
1
Order By: Relevance
“…A recent review reported that these services are only minimally beneficial to the students. 83 Although accommodations are the most common service provided to adolescents with ADHD, accommodations are not the most effective intervention for middle and high school students with ADHD. Relative to the literature on interventions for elementary school-aged children with ADHD, the extant literature on interventions for adolescents with ADHD is less vast and has only really begun to develop in the last 15 years.…”
Section: Middle School and High Schoolmentioning
confidence: 99%
“…A recent review reported that these services are only minimally beneficial to the students. 83 Although accommodations are the most common service provided to adolescents with ADHD, accommodations are not the most effective intervention for middle and high school students with ADHD. Relative to the literature on interventions for elementary school-aged children with ADHD, the extant literature on interventions for adolescents with ADHD is less vast and has only really begun to develop in the last 15 years.…”
Section: Middle School and High Schoolmentioning
confidence: 99%
“…School-Home Treatment for ADHD 3 none of which have empirical evidence to support their use 12 . Beyond these modifications, services may consist of child-centered interventions provided by school mental health providers that emphasize individual or small group counseling, with limited engagement of teachers and parents.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Students may therefore still need individualised changes to be made in the school environment, called 'accommodations', to fully participate. Accommodations are changes in timing, setting, scheduling, response or presentation of the school environment or activity that allow the student to participate in the general educational curriculum (Harrison et al 2013;Sandall, Schwartz, and Gauvreau 2016). Examples of accommodations are modifications of tasks and/or instructions (Raggi and Chronis 2006), Information and Communication Technology (ICT) such as computers and a school's virtual learning environment (Wastiau et al 2013) and special education teachers.…”
Section: Introductionmentioning
confidence: 99%